To Disclose or Not to Disclose: An Evaluation of the Effects of Information Control and Social Network Transparency. Issue 112 (January 2022) - Pu, Wenxi; Li, Siyuan; Bott, Gregory J.; Esposito, Marie; Thatcher, Jason Bennett
Abstract: Self-disclosure on Social Network Service (SNS) platforms has attracted attention in Information Systems (IS) research. While studies have investigated the effects of individual factors such as privacy concern, and trust, on SNS users' self-disclosure intention, less research has examined how characteristics of the SNS platform shape such intention. In this study, we focus on one critical characteristic of SNS platform, SNS transparency, and investigate its impact (direct and indirect via Information Control) on individuals' self-disclosure intention and the moderating role of privacy disposition. Specifically, we identify three SNS transparency features—Network Transparency, Social Presence, and Monitoring. Drawing from Communication Privacy Management Theory and Social Penetration Theory, we empirically test how these SNS transparency features directly and indirectly via Information Control influence users' self-disclosure intention. The results of our experiment show that network transparency has negative effects while social presence, as well as monitoring, have positive effects on information control. Network transparency, social presence, and information control have positive effects on self-disclosure intention. This study extends the literature by enhancing our understanding of how the SNS platform features and individual privacy disposition shape SNS users' self-disclosure intention.